Modelling and Optimization of Carbon Steel Corrosion in CO2 Containing Oilfield Produced Water in Presence of HAc - Yaro, Aprael S.; Rashid, Khalid H. (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
Previously, many empirical models have been used to predict corrosion rates under different CO2 corrosion parameters conditions. Most of these models did not predict the corrosion rate exactly, besides it determined effects of variables by holding some variables constant and changing the values of other variables to obtain the regression model. As a result the experiments will be large and cost too much. In this paper response surface methodology (RSM) was proposed to optimize the experiments and reduce the experimental running. The experiments studied effects of temperature (40 – 60 °C), pH (3-5), acetic acid (HAc) concentration (1000-3000 ppm) and rotation speed (1000-1500 rpm) on CO2 corrosion performance of the regression model calculated by RSM. The experiments were conducted in saturated solution of CO2 with 3.5 % NaCl solution. STATISTICA program version 10 was used for data analysis. In conclusion a quadratic model is proposed to predict the effect of mentioned variables in CO2 environment.